Preparation, modification and development of Ni-based catalysts for catalytic reforming of tar produced from biomass gasification. (October 2018) - Zhang, Zhikun; Liu, Lina; Shen, Boxiong; Wu, Chunfei
Abstract: Biomass gasification is one of the most promising technologies to convert renewable biomass feedstock to useful energy and chemicals for decarbonizing the current industrial activities. However, complex tar compounds are formed in the produced syngas. The presence of tar in syngas is undesirable due to a series problems caused, such as the decrease of overall efficiency and the clogging and contamination of downstream equipment. Until now, catalytic steam reforming has been widely studied for the efficient removal of tar. Previous review articles have focused on the catalytic reforming of tar by categorizing various catalysts as basic catalysts, nickel-based catalysts, non-nickel based catalysts, alkali metal catalysts, zeolite catalysts, and carbon-supported catalysts, etc. Ni-based steam-reforming catalysts have attracted much attention due to their high activity for tar reduction, low-cost and easy regeneration. However, the deactivation caused by the coke deposition and metal sintering remains the greatest challenge for the deployment of the technology. Therefore, modified Ni-based catalysts are now most frequently used for catalytic reforming of tar. At present, few review articles reported the modification of Ni-based catalysts for catalytic reforming of tar compounds. Based on this, the preparation, modification and development methods of Ni-based catalysts for catalytic reforming of tar are reviewed in this paper, aiming at promoting the catalytic performance of conventional Ni-based catalysts, in terms of high catalytic activity, long-term stability and better selectivity towards low molecular weight compounds.